Health status changes with transitory disability over time. (January 2020) - Myers, Andrew; Ward, Bryce; Wong, Jennifer; Ravesloot, Craig
Abstract: Rationale: The six-question disability set from the American Community Survey serves as the national standard for measuring disability across all surveys conducted by the U.S. Department of Health and Human Services. These questions are intended to identify people who experience a long-term disability, and data from these questions are frequently interpreted as capturing discrete groups of individuals. Recent research has shown that a significant proportion of individuals respond to these questions inconsistently over time, possibly indicating that the six-question set also identifies transitory disability. However, it is unclear if these inconsistent responses are associated with changes in health status. We begin to test the validity of these observations by exploring how changes in health related quality of life correspond to changes in disability status. Methods: We recruited 525 participants to complete a longitudinal paper and pencil survey four times over 18 months that included the six disability questions, measures of health related quality of life, and mobility equipment use. We computed within person changes in health related quality of life variables to investigate how changes in disability status are associated with changes in health status. Results: Among respondents who reported disability, half or less consistently reported the same disability. Additionally, respondents who changed disability responses also reported changes in health related quality of life. For example, when individuals transition into walking disability, their health-related quality of life index decreases by, on average, 0.18 s.d. (p<0.05), and when individuals transition out of walking disability their health-related quality of life index increases by, on average, 0.27 s.d. (p<0.001). Conclusion: The six-question set identifies people who experience both enduring and transitory disability. Changes in health related characteristics correlate with changes in disability status. This suggests that observed transitions in disability reflect real changes in perceived health and impairment. Highlights: Individuals respond to the six-question disability set inconsistently over time. The six-question set identifies both enduring and transitory disabilities. Disability change is associated with change in health related quality of life. Disability and health related quality of life change in corresponding directions.